MIGRASI PENDUDUK RESIDENSI KEDU TAHUN 1900-1911 - Sudarno Sudarno (Haluan Sastra Budaya, 2020)
In the source of population in 1900, in the Kedu Residency there was a tendency for some groups of population to migrate permanently and non- permanently to  areas  in  other  Java  and  outside  Java.  This  is  an  unusual phenomenon occurring in rural communities in Java. Because in this society for generations there have been a number of customary ties that are believed by the majority of the Javanese population to have no motive for leaving their homeland even though they are poor and rich. The customary ties in the Kedu residency have faded when the population faces a social, economic situation that is less profitable in their daily lives.